2018
DOI: 10.1093/ofid/ofy320
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Serotype Distribution of Group B Streptococcus Colonization in HIV-Infected Pregnant Women Living in Belgium: A Prospective Cohort Study

Abstract: BackgroundGroup B streptococcus (GBS) infection is a leading cause of severe neonatal infection. Maternal GBS carriage during pregnancy is the main risk factor for both early-onset and late-onset GBS disease. High incidence of GBS infection has been reported in HIV-exposed but -uninfected infants (HEU). We aimed to determine the prevalence, characteristics, and risk factors for GBS colonization in HIV-infected and HIV-uninfected pregnant women living in Belgium.MethodsBetween January 1, 2011, and December 31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Our findings are in agreement with two other prior studies, showing no difference in GBS positivity with HIV viral load greater than or less than 50 copies/mL. 9,10 Further studies are needed to fully characterize the association with detectable viral load and increased risk of GBS rectovaginal colonization. Additionally, our study found no significant differences in the GBS positivity rates among the new diagnosis of HIV during pregnancy vs the established diagnosis of HIV prior to pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are in agreement with two other prior studies, showing no difference in GBS positivity with HIV viral load greater than or less than 50 copies/mL. 9,10 Further studies are needed to fully characterize the association with detectable viral load and increased risk of GBS rectovaginal colonization. Additionally, our study found no significant differences in the GBS positivity rates among the new diagnosis of HIV during pregnancy vs the established diagnosis of HIV prior to pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in agreement with two other prior studies, showing no difference in GBS positivity with HIV viral load greater than or less than 50 copies/mL. 9 10 Further studies are needed to fully characterize the association with detectable viral load and increased risk of GBS rectovaginal colonization.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations